Recent Progress of Amorphous Nanomaterials - Kang, Jianxin; Yang, Xiuyi; Hu, Qi; Cai, Zhi; Liu, Li-Min; Guo, Lin (Chemical reviews, 2023)
Amorphous materials are metastable solids with only short-range order at the atomic scale, which results from local intermolecular chemical bonding. The lack of long-range order typical of crystals endows amorphous nanomaterials with unconventional and intriguing structural features, such as isotropic atomic environments, abundant surface dangling bonds, highly unsaturated coordination, etc. Because of these features and the ensuing modulation in electronic properties, amorphous nanomaterials display potential for practical applications in different areas. Motivated by these elements, here we provide an overview of the unique structural features, the general synthetic methods, and the potential for applications covered by contemporary research in amorphous nanomaterials. Furthermore, we discussed the possible theoretical mechanism for amorphous nanomaterials, examining how the unique structural properties and electronic configurations contribute to their exceptional performance. In particular, the structural benefits of amorphous nanomaterials as well as their enhanced electrocatalytic, optical, and mechanical properties, thereby clarifying the structure-function relationships, are highlighted. Finally, a perspective on the preparation and utilization of amorphous nanomaterials to establish mature systems with a superior hierarchy for various applications is introduced, and an outlook for future challenges and opportunities at the frontiers of this rapidly advancing field is proposed.